Enhancing Educational Governance: A Literature Review on Policy Management in Elementary Schools in Indonesia - Arifin, Fatkhul; Marini, Arita; MS, Zulela (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
This study aims to conduct a literature review on the policy of managing primary schools in Indonesia, with a focus on the development of best policies and practices that have been implemented. This research uses a qualitative approach with data collection techniques through searching and analyzing relevant literature documents. The results of the study indicate that there are several best policies and practices in managing primary schools in Indonesia. These include the school autonomy policy that provides freedom for schools to manage and develop educational programs, as well as the policy of equalization and inclusivity in education that aims to provide equal opportunities for all students. In addition, there are also best practices such as developing leadership programs for school principals, effective and efficient management of human resources, and the implementation of information technology in school administration. However, there are still several obstacles in managing primary schools in Indonesia, such as the lack of quality human resources, insufficient budget for educational program development, and lack of access to education for students living in remote areas. In order to improve the policy of managing primary schools in Indonesia, it is recommended to continue developing leadership development programs for school principals, improving the quality of human resources, and providing better support and access to students in remote areas.